Tindak Pidana Pencurian yang dilakukan Anak Usia 14 Tahun dalam Konteks Islam Menghapuskan Tindak Pidana Berdasarkan Pasal 69 Ayat 2 Undang-undang Nomor 11 Tahun 2012 Perihal Sistem Peradilan Pidana Anak (SPPA) - Citra Ayu Ramadhanti; Uu Idjuddin Solihin (Wajah Hukum, 2021)
Kids who carry out criminal demonstrations should be dealt with altruistically, went with, gave uncommon offices and foundation, sanctions given to kids as per the guideline of the wellbeing of the kid, family connections are kept up with implying that youngsters who face the law in the event that they can not be confined or detained whenever detained or confined, should be remembered for an extraordinary kid confinement room and not with grown-ups. To guarantee the assurance of youngsters who are confronted with the law is assigned collectively of kids who need unique security. In the preliminary of the adjudicator, the public examiner, specialist or other official doesn't wear robe or administration garments, shut hearings, and with a solitary judge.The creator utilizes regularizing juridical exploration strategies, specifically: a methodology that depends on the arrangements of the laws and guidelines, with the information assortment procedures in this review is to utilize the investigation of reports and every one of the information got, can be broke down efficiently to additionally dissect deliberately portraying the job of judges as far as looking at and choosing youngsters' cases with reasonable decisions, by focusing and considering the condition of the family of his folks and the natural conditions of the kid worried about the point that the kid can meet his future as well as could be expected.